The Perception Of Efl Students On The Impact Of Traveling Overseas On Their Learning Attitude - Putri, Salma Nurliza; Amiruddin, Amiruddin (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
This qualitative study was conducted to investigate the perception of students on the impact of traveling overseas on their learning attitude. The study participants were eight students from the Department of English Language Education batch 2017 who have been to Brunei Darussalam and Malaysia in 2019. The instrument used in this study was a semi- structured interview guideline. It consisted of tenpre-designed questions. Besides, there were also more questions based on the participants’ answers. The findings showed that traveling overseas makes all participants feel happy. Besides, 3 out of 8 students got new knowledge. Moreover, 3 students stated that it opened their mindset. Traveling overseas also motivated 5 students to learn English more and 6 students to become confident in speaking English. In addition, through their conversation with foreigners, 1 student said that it gives new vocabulary. It was because of their experiences there.